Standarisasi Kualitas Riset di Sekolah Dasar - Zaka Hadikusuma Ramadan (Departement of Mathematics Education, 2023)
This study aims to describe the standardization of research quality in elementary schools. The research method used is library research. The data analysis technique used is content analysis. In order to maintain the accuracy of the assessment and prevent misinformation in data analysis, bibliography checks and literature rereading are carried out. The purpose of this research is to develop a theoretical basis regarding the standardization of research quality in elementary schools. The results of this study are a comprehensive study of standardization of research quality in elementary schools including: 1) standardization of research quality including reliability and validity in a quantitative approach, 2) credibility, transferability, dependability, and confirmability are specifications for qualitative research quality standards, and 3) a similar study can be developed in the future by involving independent observers, researchers in the form of a team, and other things that support the quality assurance of research results.